1998
DOI: 10.1902/jop.1998.69.3.314
|View full text |Cite
|
Sign up to set email alerts
|

Uncontrolled Diabetes Hinders Bone Formation Around Titanium Implants in Rat Tibiae. A Light and Fluorescence Microscopy, and Image Processing Study

Abstract: This study examined the influence of diabetes mellitus on bone formation around cylindrical titanium (Ti) implants (1.0 mm in diameter and 1.5 mm in length) inserted transcortically and extending into the medullary canal of rat tibiae using light and fluorescence microscopies and image processing. Forty-eight male Wistar King A rats (age 5 weeks) were used in this experiment. Streptozotocin was injected intraperitoneally to induce diabetes and the serum glucose concentration was checked to ensure the induction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
45
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 15 publications
5
45
1
Order By: Relevance
“…Metabolic changes occurring in DM and related pathologic states such as metabolic syndrome may influence the reparative capacity of periodontal tissues 4‐15 . It is recognized that a patient must control DM before periodontal surgery; however, optimal control of the condition may be challenging for some patients 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic changes occurring in DM and related pathologic states such as metabolic syndrome may influence the reparative capacity of periodontal tissues 4‐15 . It is recognized that a patient must control DM before periodontal surgery; however, optimal control of the condition may be challenging for some patients 26 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, reduced bone turnover due to decreased production of osteoblasts, osteoclasts, osteoid, and osteocalcin has been detected 4,5 . Animal studies have demonstrated the negative impact of DM on the mechanical retention and osseointegration of implants 5‐11 . The biologic mechanisms that have been studied to validate and explain the relationship between DM and periodontal tissue alterations are: 1) gingival microangiopathy; 2) microbial changes; 3) changes in host immune response; 4) reduced production of collagen and increased collagenase; 5) defective chemotaxis of polymorphonuclear leukocytes; 12‐14 and 6) production of advanced glycosylation end products 1,15 .…”
mentioning
confidence: 99%
“…In diabetic animal models, bone-toimplant contact has been shown to be significantly reduced compared with that in non-diabetic controls (Nevins et al, 1998;Takeshita et al, 1998;Fiorellini et al, 1999). Also, the bone density adjacent to the implant in uncontrolled diabetic animals was found to be slightly, though not statistically significantly, lower than or similar to that of control animals (Nevins et al, 1998;Gerritsen et al, 2000).…”
Section: (A) Effect Of Diabetes Mellitus On the Healing Response To Dmentioning
confidence: 92%
“…In accordance with the qualitative histological observations, significantly reduced bone-to-implant contact has been reported in diabetic animals after 2, 3, 4, 8 and 12 weeks of healing following placement of titanium implants (Nevins et al 1998;Siqueira et al 2003;Ottoni & Chopard 2004), although the figures were comparable to healthy controls at 12 postoperative weeks in two other studies (Gerritsen et al 2000;Retzepi et al 2010). Furthermore, a reduction in peri-implant bone density (Gerritsen et al 2000) and up to 50% reduction in the amount of newly formed bone after the first 2 weeks of healing (Takeshita et al 1998;Giglio et al 2000;McCracken et al 2000;Siqueira et al 2003;Ottoni & Chopard 2004) have also been reported. endochondral vs. intramembranous bones and/or to differences in the implant surfaces employed, i.e.…”
Section: Preclinical Studiesmentioning
confidence: 97%